The Effect of Pregnancy in the Hemoglobin Concentration of Pregnant Women: A Longitudinal Study - Berhanu Elfu Feleke; Teferi Elfu Feleke (Hindawi Limited, 2020)
Background. The objective of this study was to estimate and identify the determinants of hemoglobin concentration before pregnancy, during pregnancy, and after labor and delivery. Methods. A prospective cohort study design was implemented. Data were collected from May 2015 to September 2018. A simple random sampling technique was used to select the participants. An interview technique was used to collect the data. Blood samples were collected before pregnancy, during each trimester, during labor and delivery, after third stage of labor, and at the 6-week postpartum period. Descriptive statistics were used to describe the profile of study participants. Generalized estimating equations were used to identify the determinants of hemoglobin concentration during each phase of pregnancy. Results. The mean hemoglobin concentrations of primigravida and multigravida before pregnancy were 12.41 g/dl and 10.78 g/dl, respectively. The hemoglobin concentration decreases with consecutive trimester reaching the lowest level at 42 days after delivery. The hemoglobin concentrations of pregnant women were decreased by hookworm 0.24 g/dl [95% CI:0.18-0.29], multiple pregnancy 0.16 g/dl [95% CI: 0.07-0.24], episiotomy 0.05 g/dl [95% CI: 0.01-0.09], gravidity 0.15 g/dl [95% CI: 0.09-0.21], age 0.03 g/dl [95% CI: 0.03-0.04], and gestational age 0.1 g/dl [95% CI: 0.09-0.11]. The hemoglobin concentration increased by iron supplementation 1.02 g/dl [95% CI: 0.97-1.07] and birth weight 0.14 g/dl [95% CI: 0.02-0.11]. Conclusion. Pregnancy significantly decreases the hemoglobin concentration of pregnant women reaching the lowest point during labor and delivery. Recommendation. Regular anemia screening intervention should be implemented after delivery.